Pengaruh Media Diorama Lingkungan Terhadap Hasil Belajar Murid Kelas II Pada Materi Kerusakan Lingkungan SDN Rejosari 01 - M. Daffa’ Syubbanul Yaum; Melani Awalia Wigati; Muhammad Eko Munandar Rifki; Aries Tika Damayani; Mintyas Budiastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of second-grade students at SDN Rejosari 01 on environmental damage material. The learning process was still dominated by lecture methods and textbooks, causing students difficulty in understanding abstract concepts. This study aimed to determine the effect of environmental diorama media on students’ learning outcomes regarding environmental damage material. The study used a quantitative approach with a pre-experimental design through a One Group Pretest-Posttest Design. The sample consisted of 27 second-grade students at SDN Rejosari 01. Data collection techniques used learning outcome tests in the form of pretests and posttests. Data analysis used descriptive quantitative analysis. The results showed an increase in students’ learning outcomes after using environmental diorama media. The average pretest score of 57.04 increased to 89.63 in the posttest. Students also became more active, enthusiastic, and easier to understand the material during the learning process. The use of diorama media helped students understand the relationship between human behavior and environmental damage concretely through three-dimensional visualization. Therefore, environmental diorama media is effective in improving elementary school students’ learning outcomes on environmental damage material.